2009
DOI: 10.4314/ari.v4i3.48688
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of aqueous extract of Ficus sycomorus l. (Moraceae) Stem Bark and Nigella sativa l. (Ranunculaceae) seeds on hematological and biochemical parameters in rabbits

Abstract: The stem bark of Ficus sycomorus and the leaves o N gella sativa were collected; dried and extracted using d stilled water and filter paper, to study the effects of combination of these extracts on hematological and biochemical parameters in rabbits. Twenty rabbits weighing between 1000 and 1,200 g were randomly separated into four groups o five rabbits each. Group A rabbits were injected with Ficus sycomorus (200 mg/kg), group B; N gella sativa (100 mg/kg), group C; combinat on of F. sycomorus (200 mg/kg) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Conversely, our extract had no effect on the RBC counts and hemoglobin level. A similar result has been reported, where no hematological and biochemical alterations were observed in rabbits injected intraperitoneally with a single or combined dose of extracts of F. Sycomorus stem bark and Nigella sativa [48].…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, our extract had no effect on the RBC counts and hemoglobin level. A similar result has been reported, where no hematological and biochemical alterations were observed in rabbits injected intraperitoneally with a single or combined dose of extracts of F. Sycomorus stem bark and Nigella sativa [48].…”
Section: Discussionsupporting
confidence: 87%
“…Generally, the cells appear pale and poorly stained, indicating a decrease in hematopoietic activity but a few areas of erythroid cells/element (white arrows) also indicate cellular recovery/regeneration. These indicate that Ficus sycomorus leaf extract stimulated erythropoiesis in accordance with studies carried out by (Sandabe et al, 2007). However at low dose Ficus sycomorus extract seems not to be effective enough to enhance full recovery from anemia.…”
Section: Discussionsupporting
confidence: 84%
“…Natives of Aninri Local Government have long used the leaf of this plant traditionally in combination with other plants to treat blood loss cases like malaria induced anemia. Studies carried out by (Sandabe et al, 2007) observed that ficus sycomorus extract can stimulate erythropoiesis in rabbits which is an indication that it may be useful in anemic situations, such as hemolytic anemia. Sycamore is a rich source of minerals e.g.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, it is used for the treatment of cough, diarrhea, skin infection, stomach disorders, liver disease, epilepsy, tuberculosis, lactation disorders, helminthiasis, infertility and sterility (Sandabe et al, 2006). The extracts of fruits of F. sycomorus are also used for the treatment of various diseases, such as cough, diarrhea, stomach disorder, skin infections, epilepsy, liver disease, tuberculosis, lactation disorder, infertility and sterility and helminthiasis (Sandabe et al, 2007;Bello et al, 2013). The target plant contains several bioactive chemical constituents.…”
Section: Introductionmentioning
confidence: 99%